2005
DOI: 10.1016/j.bbmt.2004.12.059
|View full text |Cite
|
Sign up to set email alerts
|

Allografting in patients with severe, refractory aplastic anemia using peripheral blood stem cells and a fludarabine-based conditioning regimen: The Mexican experience

Abstract: We studied the effectiveness of a fludarabine/cyclophosphamide‐based conditioning regimen without anti‐thymocyte globulin in 23 aplastic anemia patients who had no response to previous conventional pharmacologic treatment. Patients received oral busulphan 4 mg/kg/day/2 days, IV cyclophosphamide 350 mg/m2/day/3 days, and fludarabine 30 mg/m2/day/3 days. For GVHD prophylaxis, patients received MTX 5 mg/m2 days +1, +3, +6, and +11 and oral cyclosporin A (CyA) 5 mg/kg/day, starting on day −1. Peripheral blood stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…These figures are considerably lower when compared with most previous reports on allogeneic transplantation for AA. [15][16][17][18][19] Because of the small number of patients with GVHD, it is not possible to conclude from our study whether a high stem cell dose increases its risk. For haematological disorders in general, investigators have found a greater risk of chronic GVHD with PBSC transplant in the setting of a large CD34 þ cell dose.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…These figures are considerably lower when compared with most previous reports on allogeneic transplantation for AA. [15][16][17][18][19] Because of the small number of patients with GVHD, it is not possible to conclude from our study whether a high stem cell dose increases its risk. For haematological disorders in general, investigators have found a greater risk of chronic GVHD with PBSC transplant in the setting of a large CD34 þ cell dose.…”
Section: Discussionmentioning
confidence: 55%
“…Two studies have mentioned the median CD34 þ cell count but have not analysed its significance with respect to outcome, as this was not their primary study objective. 15,16 Some researchers have considered the total mononuclear cell count as a variable with potential influence on graft failure and OS. 5,6,[17][18][19] Other published studies to date have not included CD34 þ cell dose in their analysis.…”
Section: Discussionmentioning
confidence: 99%
“…17 These results reinforce encouraging survival estimates observed in previously reported studies without a comparative group, using such Flu-based regimens independently of patient age. [13][14][15][16] In older patients, the comparison of Flu-based to standard HSCT will certainly need to be further evaluated in a still larger number of patients to allow a definitive conclusion to be drawn.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Such Flu-based regimens have been explored in various nonmalignant diseases without conferring a significant survival advantage when compared to conventional myeloablative regimens. 10 In patients with SAA specifically, several previous case reports 11,12 or non-comparative studies [13][14][15][16] have reported encouraging results in the setting of HLA-matched related HSCT. The EBMT SAA working party has recently reported a favorable experience using Flu-based HSCT in SAA patients transplanted with unrelated (n=33) or family mismatched (n=5) donors.…”
Section: Introductionmentioning
confidence: 99%
“…8 In patients with SAA specifically, several noncomparative studies have reported encouraging results in the setting of HLA-matched related HSCT. [9][10][11][12][13] A recent report from the EBMT SAA working party retrospectively analyzed 30 patients older than 30 years receiving reduced-intensity conditioning HSCT (using fludarabine 30 mg/m 2 Â 4, CY 300 mg/m 2 Â 4 and most with ATG, namely a FCA regimen) and compared their outcome with a control group receiving the standard regimen (CY þ / À ATG) over the same study period (1998-2007). 14 Recipients of fludarabine-based conditioning had a higher probability of ageadjusted overall survival than the control group (P ¼ 0.04).…”
Section: Impact Of Conditioning Regimen Modifications In Older Patientsmentioning
confidence: 99%